Niveles de cuyaza en las características agronómicas y rendimiento de Cucumis sativus L., pepino regional, Loreto.2024 - Ruiz Solsol, Diana Estrella (2025)
The study site where the thesis on the effect of cuyaza levels on the cultivation of Cucumis sativus L, regional cucumber was developed was in Loreto, in which the effects of four levels of cuyaza (10, 20, 30 and 40 t/ha, corresponding to the T1, T2, T3, T4 treatments) were evaluated and DBCA statistical methods were used. ANOVA and Tukey's Test, to analyze the results that led to the conclusion of the following: A significant effect was obtained on the amount of fruits/plant in T4 and T3 with 5 and 4 respectively; likewise, a positive effect on fruit diameter in T4 with 6.9 cm and without statistical significance on fruit length that varied from 17 cm (T4 and 13 cm (T1). A significant effect was achieved on the fruit yield of the crop increasing significantly with 454 g, as well as the increase in total fruit weight per plant with 3336 g. An economic profit of S/12,343.2 was presented in the T2 treatment (20 t/ha of cuyaza).